1977
DOI: 10.1017/s0022215100084607
|View full text |Cite
|
Sign up to set email alerts
|

A multiple electrode cochlear implant

Abstract: The University of Melbourne Departments of Otolaryngology and Electrical Engineering (UMDOLEE) receiving and stimulating component of a multiple-electrode cochlear implant hearing prosthesis produces constant stimulation. It has a stimulating pulse shape that minimizes the production of toxic substances and loss of metal from the electrodes, and this is achieved with a biphasic rectangular waveform where the first phase is negative with respect to ground. The duration of each stimulus phase in 180 msec, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 18 publications
3
64
0
Order By: Relevance
“…Clinical advancements made possible by NP technology include those that restore hearing (Clark et al, 1977;Kessler, 1999;Spelman, 1999), respiration (DiMarco, 2001), bladder voiding (Brindley et al, 1982;Grill et al, 2001), and upper and lower extremity control (Kraft et al, 1992;Kralj et al, 1988;Liberson et al, 1961;Prochazka et al, 1997;Taylor et al, 1999;Weingarden et al, 1998). A subset of these prostheses communicates with neural tissue via penetrating multiple-electrode arrays (MEAs), which can provide highly specific and robust activation of the targeted neurons (Branner et al, 2001;Hillman et al, 2003;McDonnall et al, 2004;Tyler and Durand, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical advancements made possible by NP technology include those that restore hearing (Clark et al, 1977;Kessler, 1999;Spelman, 1999), respiration (DiMarco, 2001), bladder voiding (Brindley et al, 1982;Grill et al, 2001), and upper and lower extremity control (Kraft et al, 1992;Kralj et al, 1988;Liberson et al, 1961;Prochazka et al, 1997;Taylor et al, 1999;Weingarden et al, 1998). A subset of these prostheses communicates with neural tissue via penetrating multiple-electrode arrays (MEAs), which can provide highly specific and robust activation of the targeted neurons (Branner et al, 2001;Hillman et al, 2003;McDonnall et al, 2004;Tyler and Durand, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, later results confirmed that patients with implants were unable to discriminate differences in rate ≥200 to 700 Hz [7][8][27][28][29]. Field potentials from superior olivary complex in auditory brainstem of cat for 1 and 300 pps rates of simulation of auditory nerve in cochlea.…”
Section: Temporal Coding Of Frequencymentioning
confidence: 79%
“…A connector was used initially but was later found to be unnecessary if a failure occurred, because the banded electrode array could easily be slipped out and another inserted [59]. The principles underlying the electronic design of the Melbourne receiver-stimulator were elaborated in an article in 1977 [85] and a provisional patent filed in 1976 [83]. The amplitude, rate, and timing of biphasic pulses on each of 10 to 15 channels were independently controlled to stimulate an electrode array passed around the basal turn of the cochlea.…”
Section: Development Of Fully Implantable Receiver-stimulatormentioning
confidence: 99%
See 1 more Smart Citation
“…With rate of stimulation on each electrode he could distinguish pitch, but only up to 300 Hz, as shown in Figure 15 (Clark et al 1978;Tong et al 1982). This figure shows the pitch ratio versus repetition rate reached a plateau at 300 Hz.…”
Section: Psychophysics and Speech Research On Deaf Subjects With A Mumentioning
confidence: 91%